Upaya Pendekatan Kedokteran Keluarga pada Perempuan Usia 55 Tahun dengan Hipertensi di Puskesmas Banda Baro - Puan Nassya Amalia Islamy; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
A 55-year-old female patient came to the Non-Communicable Diseases Polyclinic of Banda Baro Health Center with complaints of headaches that had been felt since ± 7 days ago. The headache was felt as if it was throbbing all over the head. The headache was felt to be worse when the patient was active and stressed and reduced when the patient rested. This headache complaint had disrupted the patient's daily activities. The patient also complained of a stiff neck accompanied by weakness. The patient had been diagnosed with hypertension since 5 years ago but did not take medication regularly. The therapy received by the patient was Amlodipine 1 x 5 mg. From the results of the examination, BP was 145/90 mmHg, HR: 82 x / i, RR: 19 x / i, temperature: 36.5 ° C. Primary data was obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment is carried out based on the initial holistic diagnosis, process, and end of visit. Interventions carried out include education on the importance of a healthy lifestyle, taking medication regularly to control blood pressure and complications that can occur due to high blood pressure.